Neonatal necrotizing fasciitis - Marwah, Ashish; Marwah, Poonam; Kumar, Sunil (International Journal of Research in Medical Sciences, 2019)
Necrotizing fasciitis (NF) is an uncommon rapidly spreading infection of skin and subcutaneous tissue with systemic toxicity and fulminant course. The disease though relatively uncommon in pediatric and neonatal age group carries a high mortality unless diagnosed early and treated aggressively. Mono-microbial pseudomonas infection causing neonatal NF is a rarity and we, therefore, present one such neonate with fatal NF due to pseudomonas sepsis.